Better Students Ask More Questions.
Prove that sin^4x=cos^4x+sin^2x-cos^2x?
1 Answer | add yours
Moving cos^4 x to the left side yields:
`sin^4 x - cos^4 x = sin^2 x- cos^2 x`
Using the formula of difference of squares to the left side yields:
`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)(sin^2 x+ cos^2 x)`
Use the basic formula of trigonometry, `sin^2 x+ cos^2 x = 1` , such that:
`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)*(1)`
`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)`
The last line proves that the original identity is verified.
Posted by sciencesolve on December 20, 2011 at 2:26 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.